Wirkprinzipwechsel bei Versagen von TNF-α- Inhibitoren effektiver (Aktuelle Rheumatologie, 2017)
Gottenberg et al. Non-TNF vs Anti-TNF Treatment of Rheumatoid Arthritis After Failure of a First Anti- TNF Agent.